2009
DOI: 10.1002/nbm.1428
|View full text |Cite
|
Sign up to set email alerts
|

NMR‐based metabolomic analysis of cerebrospinal fluid and serum in neurological diseases – a diagnostic tool?

Abstract: We sought to evaluate the diagnostic accuracy of metabolomic biomarker profiles in neurological conditions (idiopathic intracranial hypertension (IIH), multiple sclerosis (MS) and cerebrovascular disease (CVD) compared to controls with either no neurological disease or mixed neurological diseases). Spectra of CSF (n = 87) and serum (n = 72) were acquired using (1)H NMR spectroscopy. Multivariate pattern recognition analysis was used to identify disease-specific metabolite biomarker profiles. The metabolite pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 45 publications
(42 reference statements)
9
103
0
Order By: Relevance
“…Oxaloacetate levels were also increased in IIH and this, together with reduced citrate, suggests alterations in the citric acid cycle. Overall the observations suggest a predominantly anaerobic environment deficient in carbohydrate substrate in patients with IIH, a conclusion supported by the presence of elevated ketone bodies 3-hydroxybutyrate (Sinclair et al, 2010) often observed in hypoxic tissues.…”
Section: Neurological Diseasementioning
confidence: 55%
See 1 more Smart Citation
“…Oxaloacetate levels were also increased in IIH and this, together with reduced citrate, suggests alterations in the citric acid cycle. Overall the observations suggest a predominantly anaerobic environment deficient in carbohydrate substrate in patients with IIH, a conclusion supported by the presence of elevated ketone bodies 3-hydroxybutyrate (Sinclair et al, 2010) often observed in hypoxic tissues.…”
Section: Neurological Diseasementioning
confidence: 55%
“…In a study of metabolite fingerprints in the CSF from patients with a range of neurological conditions we have been able to differentiate between some of these conditions by comparing the metabolites found (Sinclair et al, 2010). In particular we were able to identify some novel features of idiopathic intracranial hypertension (IIH) a neurological condition, the pathogenesis of which is poorly understood (Sinclair et al, 2008).…”
Section: Neurological Diseasementioning
confidence: 99%
“…Metabolomics provides information downstream of other techniques (e.g., genomics, transcriptomics) as well as insights into the gut microbiota and environmental exposures (4,5). The few studies that have used metabolomics in MS either examined limited metabolites or were technically unable to definitively identify many metabolites (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Establishing biomarkers of the diseases affecting central nervous system is an important goal in diagnosis and inform therapy. Metabolomics is available to define accurate disease-specific biomarkers in neurology (13).…”
Section: Discussionmentioning
confidence: 99%